The Relationship of Social Interaction to Depression Levels in the Older Adults - Simanjuntak, Minar Berliana; Pradana, Ahadi Anung (Sekolah Tinggi Ilmu Kesehatan Putra Abadi Langkat, 2021)
Background: Depression is a disorder that is often not realized either from the sufferer or the people around him, therefore depression can also be referred to as an invisible disorder and is a health problem that often occurs in the elderly by affecting social interactions. This condition can also be one of the triggers for depression in the older adults. Objective: To find out the relationship of social interaction in influencing the level of depression in the elderly. Method: The method in writing this article is through a simple approach, searching the article database using Garuda and Goggle Scholar in the last 5 years from 2016 to 2020 and getting 10 articles. The inclusion criteria used are: Indonesia language articles, articles with older adults depression, articles on the relationship of social interaction with depression in the older adults, articles on the relationship between social support dan depression in the older adults, and articles on the relationship between social status and depression in the older adults. Results: Of the 10 articles reviewed, the results of social interaction, social support, and social status that affect depression in the elderly are obtained. Most only know that depression in the elderly is an emotion or mood that changes due to the aging process. Important interventions are carried out to reduce cases of depression in the elderly and can create prosperous elderly in the future. Conlusions: The application of social interaction for the elderly who are depressed is very effective and can be applied to influence the level of depression experienced by the elderly. The application is by interacting with family or with that there will be a tone of effect for the elderly.